IMPACTO SOCIAL DE LOS MICROCRÉDITOS: CASO CÁMARA DE COMERCIO DE MILAGRO - Arteaga Estrella, Yadira (2012)
Microcredit can not be defined from a strict point of view, as a development tool used exclusively in poor countries. Currently, this tool is valid in different environments and different conditions. To manage microcredit must consider several factors that influence the effectiveness measured in terms of profit, welfare beneffic those that influence their efficiency, ie the performance of microcredit. Hence the need for formative research which gives the relationship teachers - students whose goal is to interpret the use of microcredit obtained, for the development of the productive activities of the members of the Chamber of Commerce in the city whose foundation Miracle is to improve the research culture and increase the interest we have teachers in relation to research on new processes, in search of new knowledge, foster creativity and innovation of new ideas. the purpose of the strategy is to develop skills and learning transfer through the systematization of new knowledge it is learned primarily through work in the field.